Luteolin Inhibited the Self-Renewal and Altered the Polarization of Primary Alveolar Macrophages. (18th August 2022) - Geng, Aiai; Chen, Shanze; Ren, Laibin; Zhao, Xueyi; Pei, Tianli; Jia, Bo; Gong, Daoyin
Abstract : Pure plant extract luteolin has been demonstrated to possess numerous biological and immunological effects. However, how luteolin affects mice alveolar macrophages' self-renewal and polarization closely related to inflammatory and immunomodulatory is still unknown. In our study, the transcriptomic analysis showed that several self-renewal-related pathways in luteolin-pretreated alveolar macrophages were inhibited compared to the granulocyte-macrophage colony-stimulating factor (GM-CSF)-treated group. Ki-67 staining and EdU assay indicated that luteolin inhibited GM-CSF-induced alveolar macrophage proliferation. Moreover, GM-CSF-induced expressions of c-Myc and KLF4 were significantly suppressed by luteolin at transcriptional and protein levels. Besides, we found that luteolin promoted M1 macrophage polarization induced by LPS plus IFN- γ . At the same time, it inhibited M2 macrophage polarization induced by IL-4 in both alveolar and bone marrow-derived macrophages by detecting macrophage polarization-related gene expressions at mRNA and protein levels. We found that luteolin inhibited self-renewal and altered the polarization of primary alveolar macrophages. Taken together, our data will aid in a better understanding of the immunomodulatory effects of luteolin on the primary alveolar macrophages.